If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(3-6n)=30+3n
We move all terms to the left:
-4(3-6n)-(30+3n)=0
We add all the numbers together, and all the variables
-4(-6n+3)-(3n+30)=0
We multiply parentheses
24n-(3n+30)-12=0
We get rid of parentheses
24n-3n-30-12=0
We add all the numbers together, and all the variables
21n-42=0
We move all terms containing n to the left, all other terms to the right
21n=42
n=42/21
n=2
| 7x^2-76x-28=0 | | 2q+368=882 | | -23+3m=-43 | | 2q+425=827 | | 2(w+5)=7w+5 | | 2n=-8.6 | | 103.5=9(m+3.3) | | -7=4(w+5)-7w | | -7.2+h=-13.7 | | 103.5=9(m+3.3 | | 9/2=(b-27)/18 | | 1x-3x+81=108 | | 74.9=7(m+3) | | 9=8x+ | | 1.3n-0.09=-9 | | 895=5(x+19 | | 3x+2x+4=14 | | 48=2t | | 4y+1=23 | | 8d=184 | | x+x/3=270 | | x`2+7=100 | | 7z-5=7z-z | | 3.1-|3+x|=-2.6 | | 2(y-8)-6y=8 | | 17v=119 | | 5(1+n)+2n=2(n+10) | | 5b/2+7=17 | | 5x+17=45−2x | | 10+7x-6x=8x-2x | | 3.2/100x=100 | | |3x+1|-6=-4 |